Tathbīq Tharīqah al-Tamyīz fī Ta’līm Qawāid al-Lughah al-‘Arabiyah li Tarqiyah Mahāah Qirāah Kutub al-Turās - Azizurahman, Azizurahman; Fadli, Adi; Suryani, Erma (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose- This paper describes the implementation and evaluation system of the Tamyiz method in learning Arabic grammar to improve the skill of reading heritage books in the Dinul Qoyyim Islamic Boarding School, Gunung Sari West Lombok, Halaqah Mubtadi. Design/ Methodology/Qualitative - This field research uses a qualitative descriptive analysis approach, where the data sources consist of primary and secondary data sources, using observation, interview and documentation techniques. At the same time, data analysis is done by data reduction, presentation and verification. Test the validity of the data using validity testing in the form of extended observations, triangulation, increasing accuracy, negative case analysis, and organ screening. Findings- The research findings indicate that the Tamyiz method, implemented through repetitive and varied exercises such as reading, memorization, and singing, significantly enhances students' understanding of grammar and morphology. Using the book